2019
DOI: 10.1111/den.13330
|View full text |Cite
|
Sign up to set email alerts
|

Standards of diagnostic colonoscopy for early‐stage neoplasia: Recommendations by an Asian private group

Abstract: Background and AimIn recent years, the incidence of colorectal cancer has been increasing, and it is now becoming the major cause of cancer death in Asian countries. The aim of the present study was to develop Asian expert‐based consensus to standardize the preparation, detection and characterization for the diagnosis of early‐stage colorectal neoplasia.MethodsA professional group was formed by 36 experts of the Asian Novel Bio‐Imaging and Intervention Group (ANBI2G) members. Representatives from 12 Asia–Pacif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 180 publications
(351 reference statements)
0
19
0
Order By: Relevance
“…The quality of bowel preparation plays a fundamental role in performing a high-quality colonoscopy to observe the colon mucosa [14]. Despite of the various methods for bowel preparation, the rates of inadequate bowel preparation are recorded to be between 20% and 30% [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The quality of bowel preparation plays a fundamental role in performing a high-quality colonoscopy to observe the colon mucosa [14]. Despite of the various methods for bowel preparation, the rates of inadequate bowel preparation are recorded to be between 20% and 30% [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…28 Moreover, all flat elevated lesions ≥10 mm, except serrated lesions, were classified as either laterally spreading tumour, non-granular type (LST-NG) or granular type (LST-G). [29][30][31] The lesion size was calibrated by comparisons with the closed cups of a biopsy forceps (approximately 2.5 mm). All detected lesions diagnosed as neoplastic lesions and right-sided large serrated lesions≥10 mm were removed endoscopically.…”
Section: How Might It Impact On Clinical Practice In the Foreseeable mentioning
confidence: 99%
“…Due to the high-quality colonoscopies performed by experienced endoscopists, which enabled the accurate detection of flat lesions, this study clearly showed that over 60% of detected AN were morphologically NP-CRNs, and over 80% of them were classified as LST-NG lesions. [29][30][31] Considering such a high proportion of LST-NG among detected AN and the wellknown fact that LST-NG has an easily-overlooked appearance and different oncogenic mutations in KRAS, BRAF or PIK3CA from polypoid lesions, [34][35][36] it can be postulated that LST-NG may be an important precursor of PCCRC. The relatively high proportion of LST-NG detected in the right-sided colon in this study is also in agreement with the fact that many PCCRCs are located in the right-sided colon.…”
Section: Endoscopymentioning
confidence: 99%
“…The video endoscopic system (LASEREO; Fujifilm Co.) and high-definition colonoscopes (EC-L590ZP, EC-L600ZP, and EC-L600ZP7; Fujifilm Co.) were used. Previously, the abbreviation of BLI has been used for two different words: blue laser imaging 18 and blue light imaging 19 . In this study, we noted BLI as blue laser imaging.…”
Section: Image Evaluationmentioning
confidence: 99%